Group Differences in the Value of Subscores: A Fairness Issue - Hjärne, Marcus Strömbäck; Lyrén, Per-Erik (Frontiers in Education, 2020)
The aim of this article was to examine the quality of subscores from a test fairness perspective. We were using a method based on classical test theory to study group differences in the value that subscores from a typical college admission test add to the total test score. Significant group differences in such subscore value would raise questions about fairness for that testing program. In particular, differences in subscore value between subgroups based on certain accommodations could indicate problems with the appropriateness of the accommodation. The groups in this study were males and females, and additionally a typical time adaptation given to test takers in need of extended time was analyzed. We found that the value added ratio (VAR) for all subscores in the studied test were slightly larger for males than for females. There were some differences between subgroups with respect to the extended time accommodation, but they were not systematic in the same way as for males/females. While the differences in the subscores’ added value were small in general, they may in some instances be large enough to pose a threat to a valid and fair interpretation and use of test scores.